Flood damage prediction system for disaster risk reduction - Noor Suraya, Romali; Nadiatul Adilah, Ahmad Abdul Ghani (2021)
FDAPS is a flood damage prediction system capable to forecast the expected value of flood damage corresponding to the flood depth for a flood event. It is solely based on the damage data collected from major flood event for the respective location. The flood damage is described as a percentage of the total value of the damaged property, hence it can be used for any flood event. FDAPS give the prediction of damage based on the selection of area,category, and flood depth.